Selection of developmentally competent human oocytes aspirated during cesarean section. (19th March 2018) - Duarte Alcoba, Diego; Gonsales Valério, Edimárlei; Conzatti, Maiara; Schneider, Júlia; Capp, Edison; von Eye Corleta, Helena; Brum, Ilma Simoni
Abstract: Purpose: To evaluate the efficiency/safety of Brilliant Cresyl Blue (BCB) staining as a selection method of developmentally competent immature human oocytes. Materials and methods: Immature oocytes of 32 pregnant women were recovered during cesarean section (CS). After retrieval, 92 oocytes were randomly divided into two groups: control (directly disposed to in vitro maturation – IVM) and treated – exposed to BCB 26 μM during 60 min. After staining, the treated group was classified as cytoplasm coloration, BCB positive (blue) or negative (colorless), and then disposed to IVM. Nuclear status was checked after 24 and 48 h of IVM. Nuclear maturation (polar body extrusion), meiosis resumption (absence of germinal vesicle) and degeneration rates were evaluated among the three groups (control, BCB positive and BCB negative) using Generalized Estimating Equations, followed by Bonferroni's correction for multiple comparisons. Results: Nuclear maturation was higher in BCB positive compared to BCB negative, after 24 and 48 h of IVM ( p  = .004 and p  = .032). The control group was equal to BCB positive. There was no difference among groups analyzing meiosis resumption and degeneration rates. Conclusion: The BCB test can be a good marker in pre-selection procedures of developmentally competent human oocytes aspirated during CS.